The impact of hospital language on the rate of in-hospital harm. A retrospective cohort study of home care recipients in Ontario, Canada - Reaume, Michael; Batista, Ricardo; Talarico, Robert; Rhodes, Emily; Guerin, Eva; Carson, Sarah; Prud’homme, Denis; Tanuseputro, Peter (BMC Health Services Research, 2020)
Background Patients who live in minority language situations are generally more likely to experience poor health outcomes, including harmful events. The delivery of healthcare services in a language-concordant environment has been shown to mitigate the risk of poor health outcomes related to chronic disease management in primary care. However, data assessing the impact of language-concordance on the risk of in-hospital harm are lacking. We conducted a population-based study to determine whether admission to a language-discordant hospital is a risk factor for in-hospital harm. Methods We used linked administrative health records to establish a retrospective cohort of home care recipients (from 2007 to 2015) who were admitted to a hospital in Eastern or North-Eastern Ontario, Canada. Patient language (obtained from home care assessments) was coded as English (Anglophone group), French (Francophone group), or other (Allophone group); hospital language (English or bilingual) was obtained using language designation status according to the French Language Services Act. We identified in-hospital harmful events using the Hospital Harm Indicator developed by the Canadian Institute for Health Information. Results The proportion of hospitalizations with at least 1 harmful event was greater for Allophones (7.63%) than for Anglophones (6.29%, p < 0.001) and Francophones (6.15%, p < 0.001). Overall, Allophones admitted to hospitals required by law to provide services in both French and English (bilingual hospitals) had the highest rate of harm (9.16%), while Francophones admitted to these same hospitals had the lowest rate of harm (5.93%). In the unadjusted analysis, Francophones were less likely to experience harm in bilingual hospitals than in hospitals that were not required by law to provide services in French (English-speaking hospitals) (RR = 0.88, p = 0.048); the opposite was true for Anglophones and Allophones, who were more likely to experience harm in bilingual hospitals (RR = 1.17, p < 0.001 and RR = 1.41, p < 0.001, respectively). The risk of harm was not significant in the adjusted analysis. Conclusions Home care recipients residing in Eastern and North-Eastern Ontario were more likely to experience harm in language-discordant hospitals, but the risk of harm did not persist after adjusting for confounding variables.

The health impact of living in a nursing home with a predominantly different spoken language - Batista, Ricardo; Prud’homme, Denis; Hsu, Amy T.; Guérin, Eva; Bouchard, Louise; Rhodes, Emily; Talarico, Robert; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2019)
Abundant research shows that linguistic barriers can have a negative impact on access to and quality of health care, as well as a patient's health outcomes.1–3 Establishing a culturally appropriate environment, by providing care to nursing home residents in their preferred language, is key in providing good-quality long-term care (LTC) services.4,5 French is one of Canada's 2 official languages. In Ontario, Canada, studies using population-based data have shown that Francophones have a lower perception of good health, higher prevalence of chronic diseases, and greater dependency on LTC services compared to Anglophones.6,7 However, the impact of language discordance on the outcomes of residents in nursing homes has not been previously explored.

Quality and safety in long-term care in Ontario: The impact of language discordance - Batista, Ricardo; Prud'homme, Denis; Rhodes, Emily; Hsu, Amy; Talarico, Robert; Reaume, Michael; Guérin, Eva; Bouchard, Louise; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2021)
Objectives This study compared quality indicators across linguistic groups and sought to determine whether disparities are influenced by resident-facility language discordance in long-term care. Design Population-based retrospective cohort study using linked databases. Setting and Participants Retrospective cohort of newly admitted residents of long-term care facilities in Ontario, Canada, between 2010 and 2016 (N=47,727). Individual residents' information was obtained from the Resident Assessment Instrument Minimum Data Set (RAI-MDS) to determine resident's primary language, clinical characteristics, and health care indicators. Measures Main covariates of interest were primary language of the resident and predominant language of the long-term care facility, which was determined using the French designation status as defined in the French Language Services Act. Primary outcomes were a set of quality and safety indicators related to long-term care: worsening of depression, falls, moderate-severe pain, use of antipsychotic medication, and physical restraints. Multivariable logistic regression models were used to assess the impact of resident's primary language, facility language, and resident-facility language discordance on each quality indicator. Results Overall, there were few differences between francophones and anglophones for quality and safety indicators. Francophones were more likely to report pain (10.9% vs 9.9%; P = .001) and be physically restrained (7.3% vs 5.2%; P < .001), whereas a greater proportion of anglophones experienced worsening of depressive symptoms (24.0% vs 22.9%; P = .001). However, quality indicators were generally worse for francophones in Non-Designated facilities, except for pain, which was more commonly reported by francophones in French-Designated facilities. Anglophones were more likely to be physically restrained in French-Designated facilities (6.7% vs 5.1%; P < .001). Conclusions and Implications For francophones, quality indicators tended to be worse in the presence of resident-facility language discordance. However, these findings did not persist after adjusting for individual- and facility-level characteristics, suggesting that the disparities observed at the population level cannot be attributed to linguistic factors alone.